State Discrimination Against LGBT People. Cases of Violations of Human Rights in Latin America - Estefan Vargas, Soraya (Sociedad y Economía, 2013)
Besides social discrimination and exclusion, official state regulations, judicial decisionsand positions of government are also a source of discrimination against the LGBT population.This article discusses some laws, rulings and other administrative proceedings inLatin American Countries, in order to show that the discriminatory patterns that imposea compulsory heterosexuality and normative identities are, likewise, expressed by governmentactivity, which contravenes the protection provided by the right of Human Rightsto this population.